Interfacial Laser‐Induced Graphene Enabling High‐Performance Liquid−Solid Triboelectric Nanogenerator. Issue 44 (12th September 2021) - Chen, Yun; Xie, Bin; Long, Junyu; Kuang, Yicheng; Chen, Xin; Hou, Maoxiang; Gao, Jian; Zhou, Shuang; Fan, Bi; He, Yunbo; Zhang, Yuan‐Ting; Wong, Ching‐Ping; et al.
Abstract: Laser‐induced graphene (LIG) has emerged as a promising and versatile method for high‐throughput graphene patterning; however, its full potential in creating complex structures and devices for practical applications is yet to be explored. In this study, an in‐situ growing LIG process that enables to pattern superhydrophobic fluorine‐doped graphene on fluorinated ethylene propylene (FEP)‐coated polyimide (PI) is demonstrated. This method leverages on distinct spectral responses of FEP and PI during laser excitation to generate the environment preferentially for LIG formation, eliminating the need for multistep processes and specific atmospheres. The structured and water‐repellant structures rendered by the spectral‐tuned interfacial LIG process are suitable as the electrode for the construction of a flexible droplet‐based electricity generator (DEG), which exhibits high power conversion efficiency, generating a peak power density of 47.5 W m −2 from the impact of a water droplet 105 µL from a height of 25 cm. Importantly, the device exhibits superior cyclability and operational stability under high humidity and various pH conditions. The facile process developed can be extended to realize various functional devices. Abstract : Monolithic fabrication of a flexible droplet‐based electricity generator (DEG) is demonstrated by in situ growth of laser‐induced graphene electrodes with different hydrophobicity in a fluorinated ethylene propylene‐coated polyimide bilayer structure. The DEG exhibits high power conversion efficiency, lighting up 480 LEDs with one water droplet. More importantly, the DEG exhibits superior cyclability and operational stability under high humidity and various pH conditions.